Plasma infusions in thrombotic thrombocytopenic purpura complicating systemic lupus erythematosus—a successful outcome. Issue 683 (September 1982) - Finkelstein, R.; Markel, A.; Carter, A.; Brook, J. G.
Abstract : A severe form of acute thrombotic thrombocytopenic purpura (TTP) developed in a patient with systemic lupus erythematosus (SLE). Infusions of large amounts of fresh frozen plasma (FFP) were added to steroid therapy and resulted in a rapid improvement and remission. Further episodes of thrombocytopenia and abdominal pains during a two-year follow-up were successfully treated with plasma alone and this indicates the important role of FFP infusions in the recovery of this patient.